Reconsidering the Concept of Mastautin in Malaysia: A Siyāsah syar’iyyah-Based Framework for Islamic Family Law Standardisation - Humairaa' Abdul Rahim; Anwar Fakhri Omar (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
This article examines the concept of mastautin (residence) as the jurisdictional foundation of Malaysia's Syariah courts, highlighting how decentralization yields varied legal, administrative, and doctrinal interpretations across states. Using a scoping study methodology, the research maps statutory definitions, fatwas, and administrative directives in all 13 Malaysian states and 3 Federal Territories, identifying inconsistencies and gaps in implementation. Findings reveal significant variation on residency thresholds (ranging from five days to four months), despite procedural uniformity under administrative directives (Arahan Amalan) No. 8/2019, which standardises documentary requirements such as utility bills and Imam confirmation letters. While shorter thresholds may enhance accessibility, longer ones ensure certainty, creating risk of forum shopping, unequal access, and a loss of public trust. To address these issues, the article utilises the framework of siyāsah syar’iyyah, which permits rulers to legislate public benefit (maslahah) while adhering to maqasid al-shari'ah. It states that harmonisation must progress from procedural directions towards model national norms, coordinated fatwa reviews, judicial training, and monitoring mechanisms. This study analyses Malaysia's experience within wider discussions on federalism, legal pluralism, and maqasid-based reform. This study demonstrates that siyāsah syar’iyyah provides a viable pathway to harmonize state autonomy with national unity, thereby maintaining consistency, fairness, and social responsiveness. This study contributes to the academic discourse by reinterpreting the concept of mastautin within Malaysia’s Islamic Family Law through a Siyāsah syar’iyyah-based framework. It offers a new perspective on how classical jurisprudential principles can be integrated with contemporary legal governance to achieve consistency and justice in family law administration. By proposing a model that aligns legal standardisation with the objectives of maqāṣid al-sharī‘ah, this research strengthens the theoretical foundation for harmonising diverse fiqh interpretations under modern state policy